Maize production, farm size, and tied credit in Southern Shan State, Myanmar - Fang, Peixun; Belton, Ben (International Food Policy Research Institute, 2020)
This report presents results from by far the most comprehensive survey of maize cultivators ever conducted in Myanmar. This research was designed to test characterizations of hybrid maize farming from the literature on Myanmar empirically, and identify implications for development policy and programming. Our survey represented the population of all maize growing village tracts in the nine major maize growing townships of southern Shan where the security situation at the time of the survey permitted access. A total 884 maize growing and 678 non-maize growing rural households were interviewed. We summarize key survey results and their implications below. Numbers of maize growers in southern Shan more than tripled between 2007 and 2017. Households with larger landholdings are more likely to farm maize. Many farmers grew local maize varieties before growing hybrids. Farming maize does not reduce crop diversity. Most food eaten by rural households in southern Shan is purchased. There is little difference in the value or composition of foods eaten by maize and non-maize farming households, but maize growers obtain a larger share of their food from own production than non-maize growing farm households. Maize is by far the most important crop grown the areas surveyed in terms of contribution to cash incomes. Hybrid maize seed has been adopted widely in southern Shan. Adoption of hybrid maize has been accompanied by big increases in fertilizer use. Fertilizer application and maize yields have climbed over the past decade. Maize yields vary little with farm size, but small farms apply inputs to maize more intensively than large farms. Average maize yields are lower than in other countries in the region. Women contribute 55% of all labor inputs for maize farming. Chemical inputs make up the largest share of production costs. Interest on loans amounts to just 4% of total maize production costs for households who avail credit for maize cultivation. Average gross margins for maize during 2017 were modest, but only 5% of maize growers made losses. Farms made a profit or broke even on >80% of maize harvests within the past 10 years. Returns to family labor exceed the average agricultural wage. The maize price received by farmers corresponds closely to timing of sale. Larger farms earn higher gross margins per acre on average. Most farms do not use credit to obtain maize seed and fertilizer. Most trader credit is advanced to large farms. Output-tied loans are less common than believed and taken mainly by larger farms. Taking credit does not affect the sales price obtained by maize growers.